A political spectrograph: High-resolution examinations of the United States’ ideological landscape - David Sabin-Miller; Mary C. McGrath; Marisa C. Eisenberg (PLoS ONE, 2026)
The concept of ideology is central to political discourse and dynamics, and is often cast as falling primarily on a one-dimensional scale from “left-wing/liberal” to “right-wing/conservative”, but the validity of this simple quantitative treatment is uncertain. Here we investigate and compare various high-resolution measures of ideology, both internal (self-identification and policy-stance agreements) and external (estimating the ideological position of political opinion statements). We find strong consistency between internal measures, although policy-stance agreement ideology yields a systematically centralizing and liberalizing portrait relative to more abstract “liberal/conservative” measures. More remarkably, we find that external assessments of ideology, while noisy, are largely consistent across observers, even for highly dissonant ideas and regardless of speaker identity markers. This supports the use of these responses as meaningful, comparable quantities, which general members of the public reliably project from the abstract space of political thought onto a shared one-dimensional domain.